STUDI FLUORESENS FIKOSIANIN DARI MIKROALGA Spirulina platensis DAN FOTOSENSITISASI NANOPARTIKEL TiO2 ANATASE - Supu Idawati (Jurnal Biofisika, 2013)
The electron injection (photosensitization) between titanium oxide (TiO2) nanoparticle and phycocyanin has been studied. The TiO2 nanoparticle was synthesized by sol gel method using TiCl4 as titanium source and H2SO4 as hydrolysis phase. XRD pattern showed crystalline phase (anatase phase) when annealed at temperature 600oC. According to the XRD pattern and SEM images, crystal size and particle size were 49.30 nm and 44.91 nm, respectively. The optical measurement of TiO2/phycocyanin hybrid film carried out using UV-Vis spectrophotometer. Phycocyanin has structure which conjugated double bonds, such as carboxyl (-COOH) group can be explored its potential as anchoring group to TiO2 semiconductor surface. The strongest absorption peak of phycocyanin observed at wavelength 619.36 nm with relaxation energy 2.945 eV. Moreover, the maximum emission spectrum as observed at wavelength 708.55 nm and relaxation energy 2.793 eV. It was one of the characteristic pigment suitable used as a sensitizer in solar cell. Additional of phycoyanin increased absorption spectrum from UV to visible region and indicated well efficiency in solar cell application like DSSC.